'New' Social Theory? Abbott and Social Studies of Finance. (October 2019) - Newton, Tim
This article uses an analysis of social studies of finance to explore Andrew Abbott's ideas about how we construct 'new' social theory. Drawing on Abbott, it is argued that social studies of finance tend as much towards the recycling of existing conjecture as the presentation of markedly novel argument. Yet Abbott's position also questions such potential critique by suggesting that theoretical recycling and recombination represent 'normal', and often creative, academic behaviour.